Productivity and nature of compatibility in mixed pasture of Brachiaria decumbens cv. Kluang Comel and Stylosanthes guianensis CIAT 184 under different planting ratio - Mohd Ali Hanafiah, Muhamad Hakim; Hassan, Mohammad Nasir; Thlama, Bura Paul; Malahubban, Masnindah; Mustafa, Suhaili; Kamaludeen, Juriah (Universiti Malaysia Kelantan, 2025)
This study aimed to evaluate the productivity and compatibility of Brachiaria decumbens cv. Kluang Comel (Kluang Comel) and Stylosanthes guianensis CIAT 184 (Stylo 184) under varying planting ratios. Five treatments with different ratios of Kluang Comel and Stylo 184 were tested (100G:0L, 75G:25L, 50G:50L, 25G:75L and 0G:100L). Forages were manually harvested from each polybag after seven weeks following the initial cut-back, and samples were analyzed for crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) content. Results showed that the 50:50 planting ratio of Kluang Comel and Stylo 184 yielded the highest biomass per hectare. The 75:25 planting ratio favored Kluang Comel, producing the highest leaf percentage in the grass component, while the 25:75 ratio produced the highest leaf percentage in the legume component. Increased crude protein content was observed in the 50:50 and 25:75 ratios due to the higher proportion of legume. Additionally, the 25:75 ratio yielded the highest calcium percentage. In conclusion, the 50:50 mixture of Kluang Comel and Stylo 184 is the most advantageous planting ratio, optimizing both yield and protein content. Further research is recommended to assess the longevity and nitrogen fixation capacity of the legume component to support long-term productivity in forage systems.